2021
DOI: 10.1155/2021/8432774
|View full text |Cite
|
Sign up to set email alerts
|

Potential Factors of Corneal Endothelial Cells for Progression in Children with Uveitis

Abstract: Objective. To observe the morphological changes and abnormal structure of corneal endothelial cells in children with uveitis, to analyze the related factors affecting the morphological changes of corneal endothelial cells, and to explore the clinical application of a corneal endothelial microscope in children with uveitis. Methods. The corneal endothelial cells of 70 patients with uveitis were photographed with the Topcon SP-3000 noncontact corneal endothelial microscope, and the corneal endothelial cell densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…There was a negative correlation between ECD and disease duration of PSS. Chen et al 14 have come to the same conclusion as in our study. They did a retrospective study about the CEC of 70 patients with uveitis.…”
Section: Discussionsupporting
confidence: 90%
“…There was a negative correlation between ECD and disease duration of PSS. Chen et al 14 have come to the same conclusion as in our study. They did a retrospective study about the CEC of 70 patients with uveitis.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have examined how ACI affects corneal endothelial parameters and CCT. Some of the studies indicate that the presence of ACI is associated with significantly low ECD and HEX and high CV and CCT [5,22,24]; however, other studies have found no such differences [10,41,45]. The wide variations in the findings and the lack of information underscore the importance of this systematic review and meta-analysis for clarifying the effects of ACI on the endothelium and CCT.…”
Section: Discussionmentioning
confidence: 93%